Implementation Of Criminal Sanction And Double Track System As Sentencing System On Drug Abusers In The Langkat Penitentiary Class IIA - Sri Sulistyawati, Iwan Setiawan, Rudy Pramono (International Journal of Advanced Science and Technology, 2020)
Drug traffic has gone rampant throughout the world, including in Indonesia. This research is very important to help the government program in saving young generation from drug abuse and to provide deterred effect for perpetrators of criminal act; besides that, it is also used to achieve Renstra target of UMN Al-Washliyah researches in order to cope with any problems by using legal approach formulated in the Principle of Scientific Pattern of UN Al-Washliyah, Medan with it Prioritized Research:”Study on Law ad HAM (Human Rights).The research used Research and Development (R & D) method. It was expected that the result of the research, with its title, “The Implementation of Double Track System: Imprisonment and Rehabilitation as the Punishing System for the Perpetrators of Narcotic Abuse in the Penitentiary Class II, Langkat,” could be beneficial for providing input for Law Enforcement Agency, especially in Langkat Regency in implementing Double Track System in narcotics criminal act. Keywords: double Track System, Narcotics Offense, Rehabilitation, Imprisonment.